The psychological suffering of women victims of sexual violence (Research, Society and Development, 2021)
Based on gender violence, violence against women is one of the main forms of violation of human rights, which includes the right to life, physical integrity and health. It aimed to identify the impacts that cause psychological distress in women victims of sexual violence. The method used was an integrative literature review. To search the articles to be reviewed, the PubMed, Virtual Health Library and Scientific Electronic Library Online databases were used. Carried out in the first half of 2021 between May and June, with the Health Sciences Descriptors: “Women”; "Mental health"; and “Violence against Women”. (What has big consequences? Fix this sentence) It has big health consequences, not only for women and children, but also for their families, in addition to contributing to the global burden of health problems, increasing morbidity and rates. women's mortality, including psychological trauma, fear, depression, suicide, murder, chronic pain, injuries, fractures, disability, unwanted pregnancy, inappropriate use of contraceptives, and the risk of acquiring HIV and other sexually transmitted infections. Faced with the condition of psychological stress and post-trauma frailty, the psychological suffering of sexually abused women becomes a significant theme within health care through multidisciplinarity, as it deals with the biopsychosocial well-being of the victims, evidencing a more focused look at the integrity of the social and health rights of each woman, aiming to reduce the psychological suffering commonly experienced among abused women.